Сополимеризация стирола с инденом под действием комплексного катализатора TiCl4 - AlEt2Cl; Научные труды SWORLD; Т. 28, № 1 - Ионова Е. И. Елена Ивановна; Ляпков А. А. Алексей Алексеевич; Бондалетов В. Г. Владимир Григорьевич; Зяббарова Е. Б. (2011, 2011)
Заглавие с экрана